Transformation of Urea Under Saline Condition - Sharma, J P; Chouhan, R P.S (Annals of Arid Zone, 2016)
An incubation study was carried out at 0,50, 100, 150 and 200 ppm N applied to normal soil as well as saline soil of Agra region. Soil samples drawn at different intervals after incubation were ana lysed for urea -N, N02 -N, NH4+ - N and N03- -N. Salinity of soil delayed urea hydrolysis by two days as compared to normal soil and supressed the nitrification rate but enhanced accumulation and persistence of nitrite in soil.